Elaboration of a tendency model and determination of optimal feed rate profiles for styrene/butyl acrylate semi-batch emulsion copolymerization reactor - Brahim Benyahia; M. Abderrazak Latifi; Christian Fonteix; Fernand Pla; Saci Nacef (2008)
This paper concerns mathematical modeling and validation of a lab-scale semi-batch emulsion copolymerization of styrene and butyl acrylate in the presence of n-C12 mercaptan as transfer agent. The mathematical model is developed by using reaction rate laws available in polymerization literature. The population balance equations are based on a new approach witch reduces significantly the number of the equations involved. The model is used to predict the global monomers conversion, the average molecular weights, the particle size distribution, and the amount of residual monomers. A subset of the most influential parameters of the model is identified using a parameter estimation approach by minimizing the errors between the predicted and measured data. Some parameters are also obtained from literature. The model is then validated in order to be used to compute optimal profiles of monomers feed-rates which minimize an objective function, subject to a set of tight operational constraints.